The functional reanimation of paralyzed limbs. - Loeb, G.E.
The functional reanimation of paralyzed limbs has been a longstanding goal of neural prosthetic research, but clinically successful applications have been elusive. Natural voluntary limb movement requires four major elements: actuators (i.e., motor units), sensors (i.e., somatosensory afferents), commands (i.e., cerebral cortical activity), and control (i.e., integration of the previous three elements at various levels of the neuraxis). Prosthetic equivalents of each of these elements are, as yet, primitive and often cumbersome to deploy, but new technologies promise substantial improvements for all. This article focuses on one such technology, bionic neuon (BION) modular microimplants, and its relationship to alternative and complementary technologies. The challenge remains to select and integrate them into systems that can be tailored efficiently to the widely disparate needs of patients with various patterns of weakness and paralysis.
Keywords: Actuators; Bionic neuon modular microimplants; Cerebral cortical activity; Control; Functional reanimation; Motor units; Natural voluntary limb movement; Neural prosthetics; Paralysis; Paralyzed limbs; Sensors; Somatosensory afferents